Metastable pain-attention dynamics during incremental exhaustive exercise - Slapsinskaite, A.; Hristovski, R.; Razon, S.; Balague, N.; Tenenbaum, G. (Frontiers in Psychology, 2017)
Background: Pain attracts attention on the bodily regions. Attentional allocation toward pain results from the neural communication across the brain-wide network "connectome" which consists of pain-attention related circuits. Connectome is intrinsically dynamic and spontaneously fluctuating on multiple time-scales. The present study delineates the pain-attention dynamics during incremental cycling performed until volitional exhaustion and investigates the potential presence of nested metastable dynamics.